2020
DOI: 10.1016/j.yjmcc.2020.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinases regulate ECM accumulation but not larval heart growth in Drosophila melanogaster

Abstract: The Drosophila heart provides a simple model to examine the remodelling of muscle insertions with growth, extracellular matrix (ECM) turnover, and fibrosis. Between hatching and pupation, the Drosophila heart increases in length five-fold. If major cardiac ECM components are secreted remotely, how is ECM "self assembly" regulated? We explored whether ECM proteases were required to maintain the morphology of a growing heart while the cardiac ECM expanded. An increase in expression of Drosophila's single tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 86 publications
0
7
0
Order By: Relevance
“…In mmp2 mutation or when MMP2 activity was reduced, an abnormally high concentration of Prc protein was observed in both cases (Hughes et al, 2020). Oppositely, overexpressed MMP2 showed a significant diminution of Prc network formation (Hughes et al, 2020).…”
Section: Development and Growth Of Heartmentioning
confidence: 98%
See 2 more Smart Citations
“…In mmp2 mutation or when MMP2 activity was reduced, an abnormally high concentration of Prc protein was observed in both cases (Hughes et al, 2020). Oppositely, overexpressed MMP2 showed a significant diminution of Prc network formation (Hughes et al, 2020).…”
Section: Development and Growth Of Heartmentioning
confidence: 98%
“…MMP2 also performs in the distribution of heart specific collagen, pericardin (Prc) protein (Hughes et al, 2020).…”
Section: Development and Growth Of Heartmentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have shown that MMP-mediated ECM remodeling is necessary for organ formation in the Drosophila model. It can also prevent excessive or ectopic ECM protein assembly during growth ( 113 ). The study is different from the above results, which may be explained by different models, or the regulation of MMP is a two-way process that plays different roles in different stages of tissue and organ development.…”
Section: Evaluation Of Myocardial Fibrosismentioning
confidence: 99%
“…Matrix metalloproteinases (MMPs), one of the metastasis biomarker, are extracellular calcium-dependent zinc-containing proteases, which regulate many signaling pathways involved in cell differentiation, proliferation, and metastasis [6]. In humans there are 24 MMPs, of which, 7 MMPs are GPI (Glycosylphoshatidylinositol) anchored and 17 MMPs are soluble secreted proteinases [7]. Drosophila has only two MMPs proteases, soluble secreted protease MMP1, and membrane tethered protease MMP2, making it a simple model organism for study of the involvement of MMPs in tumor metastasis [8].…”
Section: Introductionmentioning
confidence: 99%